Up to No Good? Gender, Social Impact Work, and Employee Promotions. (March 2022) - Bode, Christiane; Rogan, Michelle; Singh, Jasjit
Firms increasingly offer employees the opportunity to participate in firm-sponsored social impact initiatives expected to benefit the firm and employees. We argue that participation in such initiatives hinders employees' advancement in their firms by reducing others' perceptions of their fit and commitment. Because social impact work is more congruent with female than male gender role stereotypes, promotion rates will be lower for participating men, and male evaluators will be less likely than female evaluators to recommend promotion for male participants. Using panel data on 1, 379 employees of a consulting firm, we find significantly lower promotion rates for male participants relative to female participants, female non-participants, and male non-participants. A vignette experiment involving 893 managers shows that lower promotion rates are due to lower perceptions of fit, but not commitment, and greater bias against male participants by male evaluators. Taken together, the results of the two studies suggest that the negative effect of participation on promotion is conditional upon participant and evaluator gender, underscoring the role of gender in evaluation of social impact work. In settings in which decision makers are predominately male, gender beliefs may limit male employees' latitude to contribute to the firm's social impact agenda.